Breast cancer on the world wide web: cross sectional survey of quality of information and popularity of websites. Issue 7337 (9th March 2002) - Meric, Funda; Bernstam, Elmer V; Mirza, Nadeem Q; Hunt, Kelly K; Ames, Frederick C; Ross, Merrick I; Kuerer, Henry M; Pollock, Raphael E; Musen, Mark A; Singletary, S Eva
Abstract: Objectives: To determine the characteristics of popular breast cancer related websites and whether more popular sites are of higher quality. Design: The search engine Google was used to generate a list of websites about breast cancer. Google ranks search results by measures of link popularity—the number of links to a site from other sites. The top 200 sites returned in response to the query "breast cancer" were divided into "more popular" and "less popular" subgroups by three different measures of link popularity: Google rank and number of links reported independently by Google and by AltaVista (another search engine). Main outcome measures: Type and quality of content. Results: More popular sites according to Google rank were more likely than less popular ones to contain information on ongoing clinical trials (27% v 12%, P=0.01), results of trials (12% v 3%, P=0.02), and opportunities for psychosocial adjustment (48% v 23%, P<0.01). These characteristics were also associated with higher number of links as reported by Google and AltaVista. More popular sites by number of linking sites were also more likely to provide updates on other breast cancer research, information on legislation and advocacy, and a message board service. Measures of quality such as display of authorship, attribution or references, currency of information, and disclosure did not differ between groups. Conclusions: Popularity of websites is associated with type rather than quality of content. Sites that include content correlated with popularity may best meet the public's desire for information about breast cancer.